2006
DOI: 10.1186/1471-2164-7-210
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression profiling of human mast cells stimulated by IgE or FcεRI-aggregation reveals a complex network of genes involved in inflammatory responses

Abstract: Background: Mast cells are well established effectors of IgE-triggered allergic reactions and immune responses to parasitic infections. Recent studies indicate that mast cells may play roles in adaptive and innate immunity, suggesting an innovative view of the regulation of immune responses. Here, we profiled the transcriptome of human mast cells sensitized with IgE alone, or stimulated by FcεRI aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 46 publications
(67 reference statements)
3
45
0
Order By: Relevance
“…Apart from several exceptions, there was good overall agreement with previous profiling efforts, implying that this pathway is fairly consistent among MC subsets. [12][13][14][15][16] IL-31 was appreciably expressed in only one of the stimulated MC samples, suggesting particularly tight control. Testing MCs from 10 individuals, we found highly variable IL-31 protein levels among donors (supplemental Figure 2B).…”
Section: Changes In the MC Transcriptome Following Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from several exceptions, there was good overall agreement with previous profiling efforts, implying that this pathway is fairly consistent among MC subsets. [12][13][14][15][16] IL-31 was appreciably expressed in only one of the stimulated MC samples, suggesting particularly tight control. Testing MCs from 10 individuals, we found highly variable IL-31 protein levels among donors (supplemental Figure 2B).…”
Section: Changes In the MC Transcriptome Following Activationmentioning
confidence: 99%
“…11 Research into the full range of functional programs of a cell requires information on its specific gene-activity profile. Previous transcriptome profiling efforts concentrated either on MCs alone (eg, stimulated vs baseline [12][13][14] and MCs cultured from different sources 15,16 or at different times of development 17 ) or on comparisons between MCs and other leukocytes (either experimentally 18 or in silico 19 ). Although these studies provided valuable insights into the transcriptional landscape of MCs, they did not allow direct comparisons with nonimmune cells and were limited by the MC model(s) employed.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Additionally, in another study of human mast cell IgE-dependent activation, CD151 was reported to be significantly upregulated at 6 h (34). Out of 34 tetraspanin family members measured in these microarray experiments, only CD151 was consistently upregulated by IgE stimulation in both mouse and human arrays (data for expression of other tetraspanins not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Tetraspanin CD9 has been recently reported as a regulator of mast cells chemotaxis, where aggregation of CD9 blocked Ag- and IL-13–induced chemotaxis of bone marrow–derived mast cells (BMMCs) (33). In contrast to other tetraspanins, CD151 was reported to be specifically induced upon IgE/Ag crosslinking of FcεRI receptors in umbilical cord–derived human cells (34). However, the functional significance of expression of this tetraspanin in mast cells is not known.…”
mentioning
confidence: 99%
“…Third, in those patients with IgE autoantibodies against autoallergens, the inhibition of IgE binding to FcεRI by omalizumab and the downregulation of FcεRI would represent a central mechanism of omalizumab [101]. Other studies have followed the suggestion that mouse monoclonal IgE molecules are heterogeneous with respect to their ability to induce survival and activation events in mast cells [109].…”
Section: Omalizumab Effects On Chronic Urticariamentioning
confidence: 99%